Supply Chain Management Hierarchy Model to Support SDGs and Food Security, Using the Analytical Hierarchy Process Approach - Arie Wahyu Prananta; Indra Jaya Kusuma Wardana; I Wayan Suyadnya; Iqbal Mahcfud Fauzi (Jurnal Penelitian Pendidikan IPA, 2025)
Current global challenges, such as climate uncertainty and population growth, demand robust and sustainable supply chain management systems. Existing management models often fail to comprehensively integrate sustainability dimensions, particularly in supporting the Sustainable Development Goals (SDGs), particularly those related to food security. By combining the principles of sustainability and resilience, the proposed model is expected to serve as a guide for stakeholders in making strategic decisions to achieve a more efficient, sustainable, and crisis-adaptive supply chain, while contributing significantly to the achievement of the SDGs. The fisheries supply chain faces serious challenges in transparency, traceability, and distribution inequality, which directly impact the achievement of the Sustainable Development Goals (SDGs), particularly SDG 2 (Zero Hunger) and SDG 12 (Responsible Consumption and Production). Blockchain technology presents an innovative solution to improve data integrity and logistics efficiency.  This study aims to analyze the most prioritized blockchain implementation strategies to strengthen food security in the fisheries industry. Using the Analytical Hierarchy Process (AHP) approach, weighting of the criteria and sub-criteria influencing blockchain adoption was carried out. The results indicate that data transparency and product traceability are the top priorities in the supply chain. This study provides strategic recommendations for policymakers and industry players to accelerate the blockchain-based digital transformation of the marine and fisheries sector.